Evaluating Knowledge and Practices of Pregnant Mother’s Regarding Antenatal Care Who Attending Primary Health Care Centers In Al Hillah City - Khaleel, Muna Abdulwahab (International Journal of Psychosocial Rehabilitation, 2020)
Background: Antenatal care is universally considered as an important and basic part of Primary health care. Objective: To assess knowledge and practices of pregnant mothers regarding antenatal care who attending primary health care centers in Al-Hillah City Methodology: This study was carried out for the period from 7 / 2 / 2016 to 5 / 8 / 2016. A descriptive study design was utilized. A structured questionnaire was used as a tool for data collection. A total of 206 respondents were selected for the study. The data were collected through interview technique and by using questionnaire format. Validity and Reliability of the questionnaire were determined through panel of experts and conducting a pilot study; data were analyzed through the application of descriptive and inferential statistical analysis. Results: The results showed that (54.4%) of pregnant mothers ages were between (18-25) years, (46.6%) were illiterate, (49.5%) from moderate socioeconomic status. Half of pregnant mothers had less than five children, (99. %) were not working, (43.7%) of husbands were smokers, (47.6%) of mothers provided with health education regarding antenatal care. The results indicated that there is statistically significant of mother’s knowledge with their socio-economic status, age, and their occupational status and sources of information while no statistically significant in regard to number of living children, smoking of husbands and health education regarding antenatal care during antenatal period. Conclusions: The results of the study concluded that pregnant mothers had inadequate knowledge on specific aspects of antenatal care, while the practices of mothers were poor especially relative to taking medication without doctor prescription, performing blood test prior to the pregnancy and the need to receive tetanus toxoid vaccine during pregnancy. Recommendation(s) : Focusing on the need for more health education specifically concerning the benefits of colostrum, importance of breastfeeding, performing blood test prior to the pregnancy and receiving tetanus vaccine during pregnancy.